The association of psychological well-being and fertility intention in parents of children with intellectual disability: A foundation for reproductive education - Sepideh Sheidanik; Mitra Savabi-Esfahani; Amir Ghamarani; Amir Erfani (Wolters Kluwer Medknow Publications, 2021)
INTRODUCTION: Childbearing is an important event in a couple's life. The parents might have children with disability that affected on their well-being after the children's birth. Well-being considered as an important aspect of a couple's quality of life which may alter the future of their fertility. The present study was conducted to the association of psychological well-being and fertility intention in parents with educable intellectually disabled children. METHODS: The study was a cross-sectional descriptive research conducted on parents of children with intellectual disability (n = 386). Parents were selected randomly of schools of exceptional education and welfare. The data were collected using Ryff's scale of psychological well-being, demographic information, and fertility intention questionnaire. Data were analyzed using descriptive and analytical tests including independent t-test, Chi-square test, Mann-Whitney U-test, and Logistic regression. RESULTS: The majority of parents (83.9%) reported the negative infertility intention. Despite the mean score of well-being in parents without fertility intention (75.71 ± 11.67) was lower than parents with fertility intention (76.90 ± 11.27), the difference was not statistically significant (P > 0.05). The logistic regression analysis indicated that the parents' age and number of children with intellectual disability were predictors of fertility intention (P < 0.05), and their increase decreased the fertility intention. CONCLUSION: It seems that the lack of difference in psychological well-being scores between the two groups of parents might be due to the equal severity of disability in children. The results also indicated parents' age and the number of children correlated with fertility intention. The findings can be used to advance counseling programs in the field of healthy reproduction for this group of parents.